Three‐Phase Multiscale Modeling of a LiCoO2 Cathode: Combining the Advantages of FIB–SEM Imaging and X‐Ray Tomography. Issue 5 (22nd November 2014) - Zielke, Lukas; Hutzenlaub, Tobias; Wheeler, Dean R.; Chao, Chien‐Wei; Manke, Ingo; Hilger, André; Paust, Nils; Zengerle, Roland; Thiele, Simon
<x xml:space="preserve">Abstract</x> LiCoO2 electrodes contain three phases, or domains, each having specific‐intended functions: ion‐conducting pore space, lithium‐ion‐reacting active material, and electron conducting carbon‐binder domain (CBD). Transport processes take place in all domains on different characteristic length scales: from the micrometer scale in the active material grains through to the nanopores in the carbon‐binder phase. Consequently, more than one imaging approach must be utilized to obtain a hierarchical geometric representation of the electrode. An approach incorporating information from the micro‐ and nanoscale to calculate 3D transport‐relevant properties in a large‐reconstructed active domain is presented. Advantages of focused ion beam/scanning electron microscopy imaging and X‐ray tomography combined by a spatial stochastic model, validated with an artificially produced reference structure are used. This novel approach leads to significantly different transport relevant properties compared with previous tomographic approaches: nanoporosity of the CBD leads to up to 42% additional contact area between active material and pore space and increases ionic conduction by a factor of up to 3.6. The results show that nanoporosity within the CBD cannot be neglected.